2016
DOI: 10.26719/2016.22.7.432
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of influenza and severe acute respiratory illness incidence (burden) in three provinces of the Islamic Republic of Iran, 2012 and 2013

Abstract: There are few estimates of influenza burden in the WHO Region for the Eastern Mediterranean. In this study we estimated the burden of severe acute respiratory infection (SARI) and influenza-associated SARI (F-SARI) in selected provinces of Islamic Republic of Iran, the trends of SARI and confirmed cases of influenza (F-SARI) over 12 months (seasonality), and the age groups most at risk. Using the electronic Iranian influenza surveillance system and data of cases in sentinel hospitals of 3 selected provinces, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 8 publications
4
27
3
Order By: Relevance
“…According to WHO, fourteen of the seventeen countries that we analysed implement seasonal influenza vaccination campaign: our findings confirm that the optimal time to vaccinate is similar to Europe and North America, that is the pre‐winter Northern Hemisphere months. The scientific evidence resulting from our regional analysis complements the one obtained from individual countries; our analysis could be further enhanced by strengthening influenza surveillance networks in this region and expanding the FluNet surveillance system to neighbouring countries which currently do not report.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…According to WHO, fourteen of the seventeen countries that we analysed implement seasonal influenza vaccination campaign: our findings confirm that the optimal time to vaccinate is similar to Europe and North America, that is the pre‐winter Northern Hemisphere months. The scientific evidence resulting from our regional analysis complements the one obtained from individual countries; our analysis could be further enhanced by strengthening influenza surveillance networks in this region and expanding the FluNet surveillance system to neighbouring countries which currently do not report.…”
Section: Discussionmentioning
confidence: 67%
“…Several reports have appeared in recent years that have described the epidemiology of influenza and disease burden in single countries of this region; some others have tried to assess the impact of the annual Hajj pilgrimage to Saudi Arabia on the transmission of viral and bacterial respiratory infections, including influenza. However, no unified, comparative approach has been attempted to study the epidemiology of seasonal influenza in the Middle East and North Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In Oman, children less than 5 years had the highest influenza‐associated SARI incidence (32‐42 per 10 0000) . Another study conducted in 3 selected provinces in Iran also revealed the highest risk groups among SARI cases were children less than 5 years of age with an overall influenza‐associated SARI of 29/10 0000 [95% CI: 16.8‐43.8/10 0000] . In Kenya, most SARI cases reported were children less than 5 years of age with influenza‐associated hospitalized SARI for the same age group of 2.7/1000 [95% CI: 1.8‐3.9/1000] .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 4172 seasonal influenza virus specimens were sent to the WHO Collaborating Centres by 15 NICs and influenza laboratories of the Region during the period from 2011 to 2018. The number of seasonal influenza virus samples sent to WHO CCs for vaccine strain selection increased from 142 specimens in 2011 (median 11, IQR [4][5][6][7][8][9][10][11][12][13][14][15][16] to 1473 specimens at the end of 2018 (median 89, IQR 82-174). During the same period, the number of shipments also increased from 11 shipments per year from 8 national influenza centers during 2011 to 33 shipments per year from 15 national influenza centers and influenza laboratories at the end of 2018.…”
Section: Improved Participation In Who Influenza Vaccine Strain Selecmentioning
confidence: 99%
“…In 2011, when the second phase of the enhanced influenza surveillance programme began, no country in the Region had published any information on influenza disease burden. However, by 2018 at least eight countries in the Region had published data on the influenza disease burden and seasonality in peer-reviewed medical journals [3][4][5][6][7][8][9][10][11] leading to improved knowledge of the epidemiology of seasonal influenza in the Region (Table 4). Although, data on influenza disease burden across countries are not consistent and comparable owing to different study methods and designs used by the countries-from descriptive studies to modelling.…”
Section: Improved Knowledge Of the Burden Of Disease Associated With mentioning
confidence: 99%